THE THEME OF HOMELAND AND THE SEARCH FOR ROOTS IN B. MANSUROV’S FILM “SULTAN BEIBARS” - Absadyk, A.A.; Simonova, A.S. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
The article explores the theme of longing for one’s homeland and the search for one’s roots as a key characteristic of the protagonist’s portrayal in Bulat Mansurov’s feature film “Sultan Beibars”. In cinema, as in literature, the theme of homeland remains one of the most profound and timeless subjects, deserving attention and scholarly inquiry. The authors highlight the significance of the historical figure Beibars – upon whom the protagonist is modeled – for contemporary Kazakhstani culture.
Keywords: theme of homeland; word picture; film review; Sultan Beibars